Efficacy and Safety of the Combination of Transarterial Chemoembolization with Camrelizumab plus Apatinib for Advanced Hepatocellular Carcinoma: A Retrospective Study of 38 Patients from a Single Center - Jin-Xing Zhang; Yu-Xing Chen; Chun-Gao Zhou; Jin Liu; Sheng Liu; Hai-Bin Shi; Qing-Quan Zu (Canadian Journal of Gastroenterology and Hepatology)
Objective. To evaluate the effectiveness and safety of transarterial chemoembolization (TACE) combined with immune checkpoint inhibition (camrelizumab) plus an antiangiogenic agent (apatinib) for advanced hepatocellular carcinoma (HCC). Methods. Between March 2019 and April 2021, the clinical data of 38 patients diagnosed with advanced HCC who initially received TACE combined with camrelizumab plus apatinib were reviewed retrospectively. The objective response rate (ORR) and disease control rate (DCR) according to modified response evaluation criteria in solid tumors, progression-free survival (PFS), overall survival (OS), and adverse events (AEs) were evaluated. Results. At 2-3 months after initial therapy, the ORR and DCR was 50.0% (19/38) and 76.3% (29/38), respectively. The median PFS and OS were 7.3 months (range: 1.0–22.6 months) and 13.5 months (range: 2.3–24.3 months), respectively. Treatment-related AEs (grades 3-4) were observed in 25 patients (67.8%). No treatment-related deaths occurred. Conclusion. The combination of TACE with camrelizumab plus apatinib for the treatment of patients with advanced HCC showed promising efficacy and a manageable safety profile.